Hambor sebagai Tradisi Perdamaian: Pendekatan Kearifan Lokal Teologi Rekonsiliasi di Manggarai, Flores, Nusa Tenggara Timur - Ambun, Onessimus Febryan; Wagur, Onesimus Nggewar; Tukan, Paulus Barekama; Pangu, Robertus Bellarminus (Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
The Hambor tradition is a cultural heritage of the Manggarai people in Flores, East Nusa Tenggara, serving as a mechanism for conflict resolution and the restoration of harmony. The purpose of this research is to examine the Hambor tradition through the lens of Christian reconciliation theology, with a specific focus on its significance as a model for reconciliation rooted in local wisdom. The methodology employed in this study involves a literature review, drawing from primary and secondary sources that discuss the Hambor tradition and the principles of reconciliation theology. The results of this analysis indicate that harmony functions not only as a tool for resolving conflicts, but also as a way to nurture comprehensive social harmony through traditional practices and cultural symbols. The Hambor tradition embodies values such as forgiveness, restorative justice, and relationship mending, which are in line with the teachings of Christian reconciliation theology. In conclusion, this study argues that indigenous traditions can offer a valuable peace-building framework in diverse cultural and religious environments. By integrating aspects of local culture, Hambor presents a holistic approach to cultivating lasting peace that is compatible with Christian ethics.